Effect of manganese and ascorbic acid on the growth and yield of faba bean (Vicia faba L.) - Kadiem, Hand Jawad; Nadir, Hawrez Ali; Khraibet, Ali Abbas (Kurdistan Journal of Applied Research, 2018)
This study was carried out in field of Halabja technical college of applied sciences, Sulaimani polytechnic university, during the year 2015-2016. The objective of the study is to investigate effect of the foliar application of manganese and ascorbic acid on the growth and yield of (Vicia faba L.).The experiment contains nine concentrations and combination Mn and AsA were applied, using complete randomized block design with three replicates. The highest value of yield and number of branches were 160 g, 4.11 and 4.46 when plant applied Mn 40 ppm+ AsA 60 ppm. The maximum number of pods per plant (6.23) was given from T5 Mn 20 ppm+ AsA 30 ppm. Highest seed per pods was obtained from T8 (2.26), and the maximum 100-seeds weight was received from T2 AsA 30 ppm (45.43 g). Thus, the greatest weight of pods was found from control and T2 AsA 30ppm (13.4 g). The best length of pods and height of plant were given from both T4 Mn 20ppm and T3 AsA 60ppm (9.49 cm) (106.87 cm) respectively. The lowest seed per pods, 100-seed weight and length of pods were given from control 1.71, 36.86 g and 8.06 cm. Then the minimum yield, weight of pods, plant height, number of branches and number of pods were given from T8, T4, T5and T9 ( 41.66 g, 10.10 g, 81.98 cm, 3.25 and 4.46). From the results in this study we can recommend to applied more studies for micronutrients about different crops.